Three Physiological Components That Influence Regional Cerebral Tissue Oxygen Saturation - Suppan, Ena; Pichler, Gerhard; Binder-Heschl, Corinna; Schwaberger, Bernhard; Urlesberger, Berndt (Frontiers in Pediatrics, 2022)
Near-infrared spectroscopy (NIRS) measurement of regional cerebral tissue oxygen saturation (rcStO2) has become a topic of high interest in neonatology. Multiple studies have demonstrated that rcStO2 measurements are feasible in the delivery room during immediate transition and resuscitation as well as after admission to the neonatal intensive care unit. Reference ranges for different gestational ages, modes of delivery, and devices have already been published. RcStO2 reflects a mixed tissue saturation, composed of arterial (A), venous (V), and capillary signals, derived from small vessels within the measurement compartment. The A:V signal ratio fluctuates based on changes in oxygen delivery and oxygen consumption, which enables a reliable trend monitoring of the balance between these two parameters. While the increasing research evidence supports its use, the interpretation of the absolute values of and trends in rcStO2 is still challenging, which halts its routine use in the delivery room and at the bedside. To visualize the influencing factors and improve the understanding of rcStO2 values, we have created a flowchart, which focuses on the three major physiological components that affect rcStO2: oxygen content, circulation, and oxygen extraction. Each of these has its defining parameters, which are discussed in detail in each section.